Youth, Culture and NICTs: Triangle or Prism? - Sequeiros Bruna, Costán; Puente Bienvenido, Héctor; López Jiménez, Mélida; Fernández Ruiz, Marta (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2016)
The world changes at an unprecedented speed fuelled by globalization and technological advances, among which the new information and communication technologies (NICTs) are a central piece. Young people, keen for new experiences and products, usually position themselves at the vanguard of the use and innovation of these new technologies, adapting them to their needs and interests, creating and disseminating new modes of interaction. Issues like technological literacy, discourses around technophilia and technophobia, the idea of analogue and digital natives, etc., are concepts points of debate that are becoming increasingly central to society and deserve an in-depth consideration. But, being a novel field of research and one that is constantly evolving, research in this space finds itself facing several methodological challenges and shortcomings, but also in relation to how the object of study is defined, for example, videogames are often considered inappropriate for academic research.
Keywords: youth; digital studies; technological education; Internet; NICTs